Evaluation of Vocational Rehabilitation Services Return on Investment (VR-ROI) Models and Results - Clapp, Christopher M.; Pepper, John.; Schmidt, Robert; Stern, Steven; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open book presents the latest advances in models and data for evaluating the efficacy of vocational rehabilitation (VR) services provided to individuals with disabilities. For the first time, the VR-ROI (return on investment) model is used to simultaneously compare short- and long-term labor market outcomes across multiple state agencies and four distinct disability groups. For each disability group, the book provides information about the return on investment, as measured by the rate of return, for VR services. By offering this broad and in-depth evaluation in concert with intuitive explanations of the model and the estimation methodology, the book helps to bridge the gap between research and practice and to equip stakeholders with data-driven insights to enhance vocational rehabilitation programs for individuals with disabilities. This is an open access book.
-- Chapter 1: Introduction. -- Chapter 2: Literature Review. -- Chapter 3: Introduction to Rate of Return, Modelling, and Estimation. -- Chapter 4: National Data: What Do We Learn?. -- Chapter 5: Analysis of VR Programs in Five States. -- Chapter 6: Simplifying the Model. -- Chapter 7: Conclusions and Next Steps.
Keywords: Personnel management; Service industries; Human Resource Management; Services